2014
DOI: 10.2147/vhrm.s48923
|View full text |Cite
|
Sign up to set email alerts
|

Carotid revascularization: risks and benefits

Abstract: Despite a decline during the recent decades in stroke-related death, the incidence of stroke has remained unchanged or slightly increased, and extracranial carotid artery stenosis is implicated in 20%–30% of all strokes. Medical therapy and risk factor modification are first-line therapies for all patients with carotid occlusive disease. Evidence for the treatment of patients with symptomatic carotid stenosis greater than 70% with either carotid artery stenting (CAS) or carotid endarterectomy (CEA) is compelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 115 publications
(156 reference statements)
0
9
0
4
Order By: Relevance
“…Частота атеросклероза сонных артерий увеличивается с возрастом: у пациен-тов старше 70 лет бессимптомный стеноз каротидных артерий (более 50% просвета сосуда) отмечается у 7% женщин и более 12% мужчин [7].…”
Section: атеросклеротическое поражение сонных артерийunclassified
See 1 more Smart Citation
“…Частота атеросклероза сонных артерий увеличивается с возрастом: у пациен-тов старше 70 лет бессимптомный стеноз каротидных артерий (более 50% просвета сосуда) отмечается у 7% женщин и более 12% мужчин [7].…”
Section: атеросклеротическое поражение сонных артерийunclassified
“…В целом, у пациентов с бессимптомным стенозом сонных артерий риск гомолатерального инсульта со-ставляет в среднем 2-5% в год [7], у больных же с на-личием симптомного каротидного атеросклероза риск инсульта в течение двух лет даже при наличии опти-мального медикаментозного лечения оценивается в 26% [7]. Риск ИИ возрастает по мере прогрессирова-ния стеноза сонных артерий.…”
Section: атеросклеротическое поражение сонных артерийunclassified
“…Previous studies have demonstrated that 20% of ischemic strokes are associated with extracranial carotid artery stenosis [1, 2]. Severe stenosis of proximal internal carotid artery can cause ipsilateral cerebral watershed infarction [3].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with carotid artery stenosis, medical therapy and risk factor regulation are considered as first-line treatments. In recent decades, many clinical trials have demonstrated the benefits of carotid revascularization using carotid artery stenting (CAS) or carotid endarterectomy (CEA) in patients with symptomatic carotid stenosis more than 70% [2, 4]. Currently, CAS has become an acceptable treatment methods alternative to the standard CEA.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with carotid artery stenosis, medical therapy and risk factor regulation are first-line treatments. In recent decades, many clinical trials have demonstrated the benefits of performing carotid revascularization, which include either carotid artery stenting (CAS) or carotid endarterectomy (CEA), in the symptomatic patient population with carotid stenosis of >70% [2]. However, the question of when to perform carotid revascularization after acute ischemic stroke is still under debate.…”
Section: Introductionmentioning
confidence: 99%